Don't be a f*#king marshmallow : an illustrated guide to revolution - Mechanic, Jesse (Interlink Books, 2026)
"Don't Be a F*#king Marshmallow is an illustrated guide to changing the world--informed by the words and actions of freedom fighters like Dolores Huerta, Dr. Martin Luther King Jr., James Baldwin, Noam Chomsky, Rosa Parks, Edward Said, Angela Davis, Audre Lorde, and Fannie Lou Hamer, tied together with insight and illustrations from journalist and artist Jesse Mechanic "--